Art criticism in Colombia: The early years (2006)
This article explores some of the first examples of art criticism in Colombia. It traces the most relevant linguistic characteristics of art criticism, and shows that, in the second half of the 19th century, Colombia's first critics established a standard procedure by which to critique art. By reconstructing the polemics of 1886 and 1899, the article suggests that art critics shared a set of expectations about art that were silenced when Andrés de Santa María organized, for the first time in the country, an exhibition of modern work. The article's thesis is that critics were forced to broaden their understanding of art in order to read this new type of work. Even if this process was gradual, it points to the need to reevaluate how criticism was practiced at the time, since it has been judged as superficial and anecdotal, and therefore, of little interest. This article takes the opposing position, arguing for the need to re-examine the roots of the tradition of art criticism in Colombia in order to avoid hasty readings and erroneous perceptions of our history.